Biochemical and Cellular Mechanisms of Stress Tolerance in Plants 1994
DOI: 10.1007/978-3-642-79133-8_17
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Metabolic Engineering of Osmoprotectant Accumulation in Higher Plants

Abstract: Glycine betaine can act an osmoprotectant in many organisms.The capacity to accumulate glycine betaine in response to drought or salt stress is widespread in angiosperms, and probably appeared early in the evolution of this group. Despite the efficacy of glycine betaine, diverse angiosperm taxa have evolved a range of structurally analogous compounds which supplement or replace it.These compounds include choline-Osulfate, dimethylsulfoniopropionate, and the betaines of Balanine, proline and hydroxyproline.This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 42 publications
(24 reference statements)
1
10
0
Order By: Relevance
“…We infer that Pro and GB accumulation in G 8 might MDA content (nmol g -1 FW) have a role in its salt tolerance. Several reports on different crops are in conformity with these results (Hanson and Burnet 1994;Dubey 1997;Mansour 2000;Ashraf and Harris 2004;Mansour et al 2005;Khan et al 2007;Siddiqui et al 2008). Data revealed that NR activity in Brassica genotypes was inhibited by salt stress (Table 1).…”
Section: Resultssupporting
confidence: 66%
“…We infer that Pro and GB accumulation in G 8 might MDA content (nmol g -1 FW) have a role in its salt tolerance. Several reports on different crops are in conformity with these results (Hanson and Burnet 1994;Dubey 1997;Mansour 2000;Ashraf and Harris 2004;Mansour et al 2005;Khan et al 2007;Siddiqui et al 2008). Data revealed that NR activity in Brassica genotypes was inhibited by salt stress (Table 1).…”
Section: Resultssupporting
confidence: 66%
“…Proline accumulation in higher plants under heavy metal stress has been reported by many workers (Alia and Saradhi 1991;Bassi and Sharma 1993a,b;Hanson and Burnet 1994;Ashraf and Harris 2004;Mansour et al 2005). Although also reported in algae (Wu et al 1998), there are few reports (including those of the authors) of the effect of heavy metal stress on proline content in cyanobacteria (Wu et al 1995;Choudhary et al 2007).…”
Section: Discussionmentioning
confidence: 84%
“…Marcum and Murdoch [25] looked at the influence of salinity on the perennial ryegrass and found that with increased salinity, levels of proline and glycine betaine also increased. Proline is known to contribute to membrane stability [17] and mitigates the effect of NaCl on cell membrane disruption [24] . The results reported here for proline can be explained in view of some earlier reports that proline accumulation is one of the common characteristics in many plants under saline conditions [1,2] .…”
Section: ) Leaf Area Index Root Volume (Ml) -------------------------mentioning
confidence: 99%